Projecting the Long Arm of the Law: Extraterritorial Criminal Enforcement of U.S. Antitrust Laws in the Global Economy - Dorsey D. Ellis Jr. (Washington University Global Studies Law Review, 2002)
In this Article, I review the development, expansion, and current state of extraterritorial enforcement in the United States, look briefly at the presence or prospects of extraterritorial jurisdiction elsewhere, identify some of the problems presented by the unilateral exercise of extraterritorial jurisdiction, and suggest a view of the future.
Keywords: Globalization; International economies; Antitrust law; Expansion of municipal law jurisdiction; Extraterritoriality